Kidney Transplant Anastomosis: Internal or External Iliac Artery? - Matheus, Wagner E; Reis, Leonardo Oliveira; Ferreira, Ubirajara; Mazzali, Marilda; Denardi, Fernandes; Leitao, Victor A; Pedro, Renato N; Netto Jr, Nelson R (Urology Journal, 2009)
Introduction: We compared the best technique for arterial anastomosis in kidney transplantation, end-to-side anastomosis to the external iliac artery or end-to-end anastomosis to the internal iliac artery. Materials and Methods: A total of 38 patients with end-stage renal disease who received a kidney transplant from a deceased donor were randomized into two groups in order to undergo either end-to-end anastomosis to the internal iliac artery or end-to-side anastomosis to the external iliac artery. Length of arterial anastomosis, cold ischemia time, hospital stay, serum creatinine level, recovery of urinary output, and surgical and clinical complications during hospitalization were evaluated. After 3 years, in the patients with a functioning allograft, creatinine clearance measure, Doppler ultrasonographic study, survival, graft loss, and erectile function were compared between the two groups. Results: Postoperative analyses showed similar recovery of urinary output (P = .39) and creatinine (P = .95) between the two groups. No differences in clinical (P = .55) and surgical (P = .80) complications or in hospital stay (P = .90) were noted. The 3-year follow-up demonstrated no differences in Doppler ultrasonography results, creatinine clearance (P = .80), patient survival (P = .22), and graft loss (P = .72). Erectile dysfunction was similar, being related only to pre-operative medical history and age. Conclusion: Both techniques showed similar results in short- and long-term follow-ups. Larger prospective studies are warranted to clarify the risk of renal artery stenosis and development of erectile dysfunction.